The cemetery activity in Brazilian municipalities: Environmental impacts, legal ordinance and future perspectives - Baum, Camila; Becegato, Valter Antônio (Sustainability in Debate, 2018)
This manuscript aims to present the environmental impacts resulting from the traditional cemetery activity and the legal issues involved. Besides, it points out future trends for the destination of the bodies. For the development of this work a qualitative and exploratory approach was used, studying national and international bibliography, electronic sites and legislations linked to the subject addressed. The results of this research indicate that cemeteries are a problem for the urban planning, without a definitive resolution in the short run. The Brazilian legislation, although recent and imposing rules for the constitution of these ventures, still presents many gaps. Vertical cemeteries and crematories have gained space in the discussions and have become consolidated alternatives for the destination of bodies. However, the traditional format of cemeteries is still preference. Despite all the environmental and urbanistic impasses, the destination of bodies in horizontal cemeteries will prevail during the next decade.